Análises morfológicas, histoquímicas e ultraestruturais do tubo digestivo de tambaqui Colossoma macropomum (Cuvier, 1816) - Mori, Ricardo Hideo [UNESP] (2016)
The digestive tube of Colossoma macropomum, popularly known as tambaqui, was described by anatomic, histologic, histochemical and ultrastructural studies. Fragments of the esophagus, stomach and intestines were used for morphological and histochemical routine assays in mucosubstances. The C. macropomum has a short esophagus, a U-shaped syphon stomach with thick longitudinal folds and an intestine with circular folds related to an increase in time retention of food. Pyloric caeca were also reported in the intestine, associated with digestion and increase of the absorption surface. The esophagus showed a stratified epithelium composed of epithelial cells with fingerprint-like microridges on the cellular surface and goblet cells with cytoplasm filled with secretion granules composed of neutral and acid mucosubstances. The stomach was divided into the glandular cardic and fundic regions and aglandular pyloric region with pyloric sphincter. The lining gastric epithelium was simple columnar with apical mucosubstances that protects the mucosa. The intestine has a simple columnar epithelium mainly composed of enterocytes with apical microvillis and goblet cells that increased in number in the aboral direction. Goblet cells had secretion granules for protection, lubrication and transformation of food in chyme. Rodlet cells were also reported in the intestinal epithelium associated with the immune system of teleosts. The results correlated the morphofunctional characteristics of the digestive tube of C. macropomum with other species with different feeding habits, contributing to the development of nutritional studies for the improvement of Brazilian fish culture